Age is not a significant predictor of survival in patients with IDH-wildtype glioblastoma that undergo gross total resection and complete adjuvant chemoradiation - Cozzens, Jeffrey W.; Drewes, Noah B.; Delfino, Kristin R.; Chin, Kayla L.; Amin, Devin V.; Lokaitis, Barbara C.; Espinosa, José A.; Jones, Breck A.; Acakpo-Satchivi, Leslie J.; Dayoub, Hayan; Frankel, M. Bruce; Agamah, Edem; et al. (Frontiers in Oncology, 2025)
BackgroundOlder age is often cited as a negative prognostic factor for individuals with glioblastoma, but it is unclear if this is true when other prognostic factors are equalized.MethodsThis study is an observational, single-center retrospective analysis of data from consecutive individuals with histologically identified high-grade glioma prospectively accumulated for a registry of all neurosurgical operations in our region from 2010 to 2024 (15 years). Data concerning histology, survival, IDH mutations, MGMT methylation status, extent of resection, frailty (measured by m-Fi-5 index) and subsequent adjuvant treatment (radiation and chemotherapy) were all recorded. Statistical analysis was performed on selected groups with Kaplan-Meier survival analysis, Student’s t-test and multivariable Cox proportional hazards regression.ResultsThere were 270 individuals who underwent a neurosurgical procedure resulting in a histopathological diagnosis of glioblastoma. The data from a select group of 91 individuals were examined where all individuals had tumors with IDH-wildtype, gross total resection, and treated with chemoradiation. When univariately assessing for the impact of age on survival, no significant association was found (p=0.5380). After adjusting for MGMT methylation status and frailty, age remained insignificantly associated with overall survival (p=0.4009).ConclusionsAge does not seem to be a factor in overall survival for glioblastoma when all the other prognostic factors are equalized. The idea that younger age is a positive prognostic factor is probably the result of more frequent IDH-mutant tumors in younger patients, increased incidence of frailty in older patients and the unwillingness of healthcare providers and patients/families to aggressively treat older patients.